1998
DOI: 10.1097/00007890-199812270-00006
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Preemptive Therapy of Posttransplant Lymphoproliferative Disease in Pediatric Liver Recipients1

Abstract: Since instituting this protocol, the overall incidence of PTLD has fallen from 10% to 5% for children receiving primary tacrolimus therapy after OLT. No high-risk pediatric liver recipient treated preemptively with intravenous ganciclovir developed PTLD. Both children with PTLD were less than 1 year at OLT and considered low-risk. However, their positive EBV antibody titers may have been maternal in origin and not have offered long-term protection. Serial monitoring of EBV-PCR after pediatric OLT is recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
244
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(248 citation statements)
references
References 44 publications
2
244
0
2
Order By: Relevance
“…EBV activity can be assessed in a number of ways, including evaluation of EBV viral load in the peripheral blood (as measured by PCR amplification), measurement of the number of EBV-infected peripheral blood mononuclear cells, and ex vivo spontaneous growth of EBV-transformed B cells. [32][33][34][35][36][37] Serology for antibodies to EBV viral capsid antigen or nuclear antigen is less sensitive than these methods, but is more specific for EBV disease; however, these tests are not routinely available in all clinical chemistry labs and thus results may be delayed. By all of these measures, it has been demonstrated that EBV activity is greater in transplant recipients with PTLD than in transplant recipients without PTLD, healthy EBV-seropositive adults, or healthy adults with infectious mononucleosis.…”
Section: Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…EBV activity can be assessed in a number of ways, including evaluation of EBV viral load in the peripheral blood (as measured by PCR amplification), measurement of the number of EBV-infected peripheral blood mononuclear cells, and ex vivo spontaneous growth of EBV-transformed B cells. [32][33][34][35][36][37] Serology for antibodies to EBV viral capsid antigen or nuclear antigen is less sensitive than these methods, but is more specific for EBV disease; however, these tests are not routinely available in all clinical chemistry labs and thus results may be delayed. By all of these measures, it has been demonstrated that EBV activity is greater in transplant recipients with PTLD than in transplant recipients without PTLD, healthy EBV-seropositive adults, or healthy adults with infectious mononucleosis.…”
Section: Surveillancementioning
confidence: 99%
“…Although the studies were small, negative predictive values (94-100%) and sensitivities (100%) were quite high. 36,37,39 It is interesting to note that EBV DNA levels decrease with anti-EBV therapy, 35,37 although this may not always correlate with the PTLD tumor response. 40 Thus, while measurement of EBV viral load is biologically appealing as a predictive test, the clinical utility remains to be determined.…”
Section: Surveillancementioning
confidence: 99%
“…Bacterial and fungal infections affect up 75% of patients and directly result in up to 50% of deaths. 1,11 Multiresistant organisms, such as methicillin-resistant Staphylococcus aureus, multiresistant Klebsiella, and vancomycin-resistant enterococcus, [25][26][27][28] The immunosuppressive management of neonates is difficult and rarely tailored to age. In most centers, neonates receive regimens similar to those for older patients, with protocols based on either cyclosporine or tacrolimus.…”
Section: Operative and Postoperative Considerationsmentioning
confidence: 99%
“…1, EBER-1, LMP have been used to identify patients at risk for PTLD, especially in the pediatric and allogeneic bone marrow transplant populations (11)(12)(13)(14)(15)(16). These two patient populations are particularly at high risk for PTLD, given the lack of EBV immunity in most pediatric patients and the high level of immunosuppression and the altered immune system seen in T-cell depleted or mismatched allogeneic bone marrow transplants.…”
Section: Ebv Pcr For Diagnosis and Monitoring Of Ptldmentioning
confidence: 99%